ENHANCEMENT OF PRIMARY CARE ASSESSMENT TOOL (PCAT): A SCOPING REVIEW - Dewi Surya Ningsih; Antono Surjoputro; Syamsulhuda Budi (Jurnal Administrasi Kesehatan Indonesia)
Background: Strengthening the quality of primary health care is one way to improve public health. For this reason, an appropriate primary care assessment tool (PCAT) is necessary to evaluate and improve primary health care.